Self-Learning Strategies for EFL Acquisition among Saudi University Students - Oraby, Khaled; Alaraj, Mamoon (International Journal of Language and Literary Studies, 2024)
This study investigates self-learning strategies for English as a Foreign Language (EFL) acquisition among Saudi university students. Despite the importance of English proficiency, many Saudi students struggle to achieve the desired level of competence. This research aims to identify effective self-learning strategies that can empower students to enhance their EFL skills independently. Using focus groups and a questionnaire, the study explores the most common and inspiring self-learning strategies adopted by Saudi university students, as well as the reasons behind their preferences. The findings reveal that watching American movies and TV shows, taking online courses, and engaging with English-language media are among the most popular strategies. Traveling to English-speaking countries, watching American TV shows, and reading English stories are considered the most inspiring approaches. The study provides valuable insights for educators, policymakers, and curriculum developers to design more effective English language programs tailored to the needs and preferences of Saudi university students. By understanding and promoting these self-learning strategies, this research aims to contribute to improving EFL proficiency and empowering Saudi students to succeed in an increasingly globalized world.